Detection of prions in oocytes and ovaries of ewes naturally infected with classical scrapie - Paula A. Marco Lorente; Maialen Zinkunegi; Diego Sola; Nerea Larrañaga; Belén Marín; Bernardino Moreno; Juan J. Badiola; Rosa Bolea; Alicia Otero (Veterinary Research)
Abstract Classical scrapie is a prion disease that affects goats and sheep and is transmitted mainly horizontally. However, infection can also occur vertically, from mother to offspring, but the exact mechanism is unclear. The possibilities include transmission during pregnancy, birth, or after birth. Some studies have reported that prions are present in various reproductive tissues and fluids, suggesting that vertical transmission could occur through the germ line. However, the presence of prions in female reproductive tissues and oocytes has not been extensively studied, so their role in vertical transmission is unknown. Oocytes and ovarian tissues from 25 naturally infected ewes (ARQ/ARQ and VRQ/VRQ genotypes) and healthy controls were analysed. The samples were subjected to PMCA for prion detection. Histopathological and immunohistochemical evaluations of ovarian tissues were also performed. We demonstrated that PrPSc can accumulate in the oocytes and ovaries of scrapie-infected ewes, indicating a potential germline route of transmission. Prion accumulation appears to be influenced by the host genotype and prion strain, emphasizing the need for ultrasensitive detection techniques. Further research under controlled conditions is necessary to elucidate the mechanisms and implications for disease control and breeding programs.